2022
DOI: 10.1080/1747423x.2021.2018514
|View full text |Cite
|
Sign up to set email alerts
|

Forest Transitions in the United States, France and Austria: dynamics of forest change and their socio- metabolic drivers

Abstract: Understanding the drivers of forest transitions is relevant to inform effective forest conservation. We investigate pathways of forest transitions in the United States (1920–2010), France (1850–2010), and Austria (1830–2010). By combining evidence from forest inventories with the forest model CRAFT, we first quantify how change in forest area ( ΔA ), maximum biomass density ( ΔBd max ), and actual biomass as fraction of maximum biomass ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 119 publications
(155 reference statements)
1
4
0
Order By: Relevance
“…This could already reflect a first sign of the subsiding rejuvenation through the age-structure effect in the NE. In fact, this is in line with previous research showing that simultaneous growth of harvest and C stock density may be feasible only temporarily for few decades (Gingrich et al, 2022).…”
Section: Northeast and Southeast: Fire Suppression Rejuvenation And S...supporting
confidence: 90%
“…This could already reflect a first sign of the subsiding rejuvenation through the age-structure effect in the NE. In fact, this is in line with previous research showing that simultaneous growth of harvest and C stock density may be feasible only temporarily for few decades (Gingrich et al, 2022).…”
Section: Northeast and Southeast: Fire Suppression Rejuvenation And S...supporting
confidence: 90%
“…Perceived declines in forest products and services in the southern states in the U.S. were described as driving efforts by institutional actors to incentivize tree planting [ 26 ]. Displacement of forest products was only identified as a driver in one case study; instead, research illustrated that transitions in the United States and Europe were affected by a major reduction in firewood use with fossil fuel substitution [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight forest transition case studies estimated carbon sequestration-related outcomes. Of these, three case studies in Europe and the United States concluded that in addition to forest area expansion, vegetation thickening contributed to growth in forest carbon sequestration [ [27] , [28] , [29] ]. In contrast, modest gains in Brazilian Atlantic forests after the early 2000s were reversed due to re-clearing of regenerated forests [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, many forests, mainly in the temperate and boreal regions with a long land-use history, are not in equilibrium. After periods of strong depletions followed by periods of reduced wood harvest pressures, forests enter a dynamic situation of regrowth, which allows for increasing harvest rates without depleting forest biomass stocks 12 -the fundament of the ''sustainable forestry'' principle. In such situations, even if forest biomass increases over time, harvest ''prevents'' the forest carbon stock to reach maturity.…”
Section: Adding the Time Dimension To The Equationmentioning
confidence: 99%